Factors Related to The Implementation of Early Breastfeeding Initiation (Imd) By Midwives In Bireuen District - Khairunnisak, Khairunnisak; Sari, Fatimah; Kasjono, Heru Subaris (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
In 2022, the percentage of newborns receiving IMD nationally was 86.5 %. The province with the highest percentage of newborns receiving IMD was DKI Jakarta Province (99.2%), while the province with the lowest percentage was Bali Province (63.0%). The national IMD target for 2022 was 62%, so all provinces have achieved the target. However, several provinces still have low IMD coverage compared to other provinces in Indonesia, namely Bali (63.0%), North Sumatra (67.7%), North Sulawesi (72.4%), Maluku (75.7%) and Aceh (78.5%). The research method was cross-sectional. The sampling technique was a total sampling of 71 midwives. The results of the study showed that of the 6 variables studied, there were education (0.003), knowledge (0.001), trust (0.023) and variables that had a p value > 0.05, namely training (0.152), attitude (0.329) length of service (0.302) and family support (0.799) meaning that education, knowledge, and trust are related to the implementation of Early Breastfeeding Initiation in Bireuen Regency in 2024. The conclusion is that there is a relationship between education, knowledge, and trust related to the implementation of Early Breastfeeding Initiation in Bireuen Regency in 2024.